SEMUKUK INDAH BEACH MANAGEMENT STRATEGY FOR OPTIMIZING REGIONAL INCOME AND EMPOWERING THE COMMUNITY OF PAUH TANJUNG IMAN VILLAGE - Pujiyanto, Di'a; Verawati, Heni; Susanti, Eka Desi (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
Semukuk Indah Beach is a source of regional income for the community in Pauh Tanjung Iman Village, but currently the beach rarely receives maintenance such as cleaning up rubbish and maintaining existing facilities and infrastructure. The aim of the service is to analyze the management strategy for Semukuk Indah Beach to optimize regional income and empower the people of Pauh Tanjung Iman Village. The method for the community service program implemented in Pauh Tanjung Iman Village is by coordinating and discussing with village officials and community leaders in the village both online and offline. The research results show that the management strategy for Semukuk Indah Beach to optimize regional income is carried out by promoting tourist attractions through social media, namely Tiktok and Instagram. Then, to increase the number of visitors at Semukuk Indah Beach, the beach location was repaired and cleaned so that it was clean, orderly and beautiful. Furthermore, community empowerment is carried out by maintaining the cleanliness of the beach environment by completing the necessary facilities and infrastructure such as providing trash bins